Lophodermella needle cast pathosystem: the phylogenetic relationships, host-mycobiota interactions, and molecular diagnosis of Lophodermella pathogens on Pinus - Ata, Jessa Pude, author; Stewart, Jane E., advisor; Abdo, Zaid, committee member; Kim, Mee-Sook, committee member; Mondo, Stephen J., committee member; Norton, Andrew P., committee member (Colorado State University. Libraries, 2022)
The impact of needle diseases in conifer stands has increased worldwide due to regional variations of warmer and wetter climates that spur the activity of needle pathogens. Heavy needle cast infection results in loss of growth among pine stands which can lead to losses in biomass production and decline in ecosystem goods and services. Despite this threat, a well-informed disease management strategy is lacking due to limited research on many needle pathogens that remain to have unclear taxonomy, uncharacterized fungal biology, and unknown trophic lifestyles and interactions. Thus, this research applied molecular tools to understand conifer needle pathosystems, particularly Lophodermella needle casts that have caused epidemics on Pinus contorta stands in Colorado, USA. Specifically, this research aims to analyze the phylogeny of Lophodermella species using molecular data and identify shared derived characters for taxa delimitation; investigate the interaction of the mycobiota and the P. contorta host in healthy versus diseased states; and develop molecular tools for the rapid diagnosis of Lophodermella needle cast. To achieve these objectives, this research is divided into five chapters. The first chapter gives an overview of the emerging needle diseases worldwide and the needle cast epidemics on P. contorta in Colorado caused by Lophodermella concolor and L. montivaga. It discusses current knowledge on the Lophodermella pathogens and management strategies for needle diseases. The second chapter highlights the relationship of Lophodermella species from North America (L. arcuata, L. concolor and L. montivaga) and Europe (L. sulcigena and L. conjuncta), and their potential synapomorphic characters. It also revealed a newly identified, genetically unique rhytismataceous species on Pinus flexilis that is morphologically similar to L. arcuata. The third chapter discusses the adverse impact of the diseases to needle mycobiota and the defense strategies of the P. contorta host. It further shows, for the first time, the endophytic lifestyle of Lophodermella pathogens on P. contorta. The fourth chapter details the efficiency of the PCR- based markers developed from multi-copy and single-copy gene regions to identify and detect L. concolor and L. montivaga on P. contorta, and L. arcuata and Bifusella linearis on P. flexilis. And lastly, the fifth chapter summarizes the important results of this research and discusses their potential implications on the management of emerging needle diseases. My dissertation closes with recommendations on future research that will address further questions of needle diseases caused by Lophodermella species and other pathogens.
Keywords: molecular marker; tree microbiome; plant disease; fungal pathogen